2012
DOI: 10.1016/j.lungcan.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with smoking abstinence among smokers and recent-quitters with lung and head and neck cancer

Abstract: Introduction Smoking cessation among cancer patients is critical for improving outcomes. Understanding factors associated with smoking abstinence after the diagnosis of cancer can provide direction to develop and test interventions to enhance cessation rates. The purpose of this study was to identify determinants of smoking outcomes among cancer patients. Methods Standardized questionnaires were used to collect data from 163 smokers or recent-quitters (quit ≤ 6 mo) at study entry of which 132 and 121 had dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 45 publications
6
55
2
Order By: Relevance
“…Most studies were conducted in the United States (60.3%, n =79; e.g., (74, 99, 101, 114, 134)), with the next most common study locations being in Canada (7.6%, n =10; (30, 38, 39, 44, 65, 84, 97, 104, 147, 148)) and France (4.6%, n =6; (32, 37, 100, 108, 113, 146)). Most papers described cross-sectional studies (75.6%, n =99), but some described longitudinal studies (24.4%, n =32) (10, 35, 38, 42, 45, 46, 52-54, 56, 62, 65, 69, 73, 75, 76, 80, 84, 89, 90, 98, 100, 103, 104, 118, 121, 123, 126, 129, 135, 149, 152). For the longitudinal studies, the number of tobacco use assessments ranged from two (e.g., (42, 100, 123)) to ≥ 5 (e.g., (69, 103, 121)); the number of assessments was sometimes unclear (e.g., (35, 118, 152)).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were conducted in the United States (60.3%, n =79; e.g., (74, 99, 101, 114, 134)), with the next most common study locations being in Canada (7.6%, n =10; (30, 38, 39, 44, 65, 84, 97, 104, 147, 148)) and France (4.6%, n =6; (32, 37, 100, 108, 113, 146)). Most papers described cross-sectional studies (75.6%, n =99), but some described longitudinal studies (24.4%, n =32) (10, 35, 38, 42, 45, 46, 52-54, 56, 62, 65, 69, 73, 75, 76, 80, 84, 89, 90, 98, 100, 103, 104, 118, 121, 123, 126, 129, 135, 149, 152). For the longitudinal studies, the number of tobacco use assessments ranged from two (e.g., (42, 100, 123)) to ≥ 5 (e.g., (69, 103, 121)); the number of assessments was sometimes unclear (e.g., (35, 118, 152)).…”
Section: Resultsmentioning
confidence: 99%
“…Efforts are ongoing to improve tobacco cessation efficacy in patients with cancer, including consideration of psychological or behavioral comorbidity, social environment, and diseaserelated variables. [24][25][26][27][28][29][30] These efforts may ultimately result in improved tobacco cessation outcomes, but they will not be realized if patients are not offered tobacco cessation support. Improved education and training may be needed, but improving access to dedicated cessation support is also necessary to improve overall tobacco cessation outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Warren et al demonstrate that 29.4 % of head and neck cancer patients require biochemical confirmation for accurate assessment of tobacco use [22]. Cooley et al also demonstrate that 18.9 % of smokers misrepresent true tobacco use on follow-up evaluation [41]. The authors are unaware of any studies that have evaluated the accuracy of self-reported tobacco use in breast cancer patients, but our results demonstrate a consistent finding that misrepresentation occurs in patients with tobacco-related or non-tobacco-related cancers.…”
Section: Discussionmentioning
confidence: 99%